Mid-term impact of mild-moderate COVID-19 on cardiorespiratory fitness in élite athletes - Anastasio, F.; La Macchia, T.; Rossi, G.; D`Abbondanza, M.; Curcio, R.; Vaudo, G.; Pucci, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Mid- and long-term sequelae of COVID-19 on cardiorespiratory fitness are unknown. Aim of the study was to assess the mid-term impact of mild-moderate COVID-19 on cardiorespiratory fitness evaluated by cardiopulmonary exercise testing (CPET) in élite athletes. METHODS: 13 elite cross-country skiers with previous mild-moderate COVID-19 symptoms underwent CPET before resuming seasonal training (COVID athletes). 13 élite detrained cross-country skiers, matched for principal confounding factors, were taken as controls (control group). Resting peripheral oxygen saturation, pulmonary function test, echocardiography, bioelectrical impedance analysis and CPET (modified XELG2, Woodway, USA) were performed in all participants. RESULTS: Median recovery time in COVID athletes was 34 days (IQR 33-38 days). COVID athletes reached earlier the onset of the aerobic threshold (4`48" vs. 6`28", R2=0.15, F=4.37, P<0.05) than controls, whereas the time to anaerobic threshold and maximal efforts did not significantly differ between groups. Oxygen consumption was lower at the aerobic threshold in COVID athletes than controls (VO2/kg 28.6 mL/min vs. 38.9 mL/min, R2=0.39, F=15.34, P<0.01), whereas no significant difference between groups was found both at the aerobic threshold and at peak exercise (all P<0.05). Findings from resting echocardiography and pulmonary function test were similar between the two groups. CONCLUSIONS: Élite cross-country athletes, previously affected by mild-moderate COVID-19, reached earlier the aerobic threshold than controls, whereas the remaining CPET parameters did not differ between groups. Such changes were not associated with any detectable difference in resting pulmonary and cardiac examination. Subjects affected by mild-moderate COVID-19 may require a longer time course of re-adaptation to aerobic exercise.